Technology Integration in Curriculum Management: Digital Literacy Strategy in Basic Education in Indonesia - Salma, Fidela Restu; Wulandari, Isnaeni Putri; Badriyah, Laelatul (UM Purwokerto Press, 2025)
The importance of adaptation in the digital age is driving educational institutions to integrate technology for the relevance of the learning process. This directly affects curriculum management, where technology improves efficiency and quality. However, its implementation in Indonesia is still constrained by access gaps and low digital literacy of teachers and students. A holistic strategy that includes continuous training and multi-stakeholder collaboration is needed to optimize the potential of technology integration, improve education quality and prepare learners for global challenges.